Effects of Temperature and Aging Time on Oil Recovery in Carbonate and Sandstone Reservoirs using Sea-Water - Naser, Madi; Erhayem, Mohamed; Abdullah, Hesham; Amer, Muammer; Mohamed, Abdalsalam (Journal of Pure & Applied Sciences, 2018)
The present paper summarizes a laboratory study to compare the effect of seawater with different crude oils, temperatures, and aging times on oil recovery in carbonate and sandstone reservoirs. The sandstone and carbonate cores were submerged in the brine solution and then placed in the oven at 70°C to simulate realistic reservoir conditions. The seawater was allowed to imbibe into the cores, displacing oil out of the cores until equilibrium was reached. The result shows that the impact of seawater on oil recovery in sandstone was higher than in carbonate. At higher temperatures, the oil recovery was more moderate than at low temperatures.